A polygonal finite element method for shakedown analysis of structures - Ho, Phuc L. H.; Le, Canh V.; Nguyen, Phuong H.; Tran, Dung T. (Vietnam Journal of Mechanics, 2023)
This study presents an innovative numerical method that combines the polygonal finite element method (Poly-FEM) with conic optimization techniques within the framework of structural shakedown analysis. The resulting optimization problem is formulated as a second-order cone programming (SOCP) problem and is efficiently solved using the MOSEK primal-dual interior-point solver. Numerical experiments validate the computational efficiency and efficacy of the proposed approach.